PEMBUATAN MEDIA SLIDE SUARA UNTUK MATA PELAJARAN SEJARAH SMU - Rokhman, M Nur; Murdyastomo, HY. Agus (Universitas Negeri Yogyakarta, 2005)
History teachers at senior high schools in the Kulon Progo Regency were given training in making audio-slide media with the objectives of im proving the quality of history teaching at those schools, enabling those teachers to acquire via given lectures, demonstrations, and exercises the knowledge and skills in making audio-slide media, and arousing the creativ ity that would enable them and make them willing to make their own audio-slide media. An attempt to solve the problem of achieving those objectives was made by means of lectures about the importance of media in general in teaching-learning activities, lectures about making audio-slide media, train ing in making such media, practice in making them, and evaluation of the results.The activities in carrying out that public service involving applied science and technology were conducted through lectures followed with question-and-answer sessions, lectures followed with demonstrations, train ing and tutorials, and practice in making audio-slide media.The activities resulted in the participants gaining knowledge, skills, and experience in making such media. Coordination with the MGMP, the organization developing working teachers' expertise, ran well; the training was held at a state senior high, SMU N I Sentolo, on Wednesdays (the MGMP day for senior high history teachers). Twenty teachers participated and two sets of audio-slide media for Grade-l class materials with two to pics: historical sources, evidence, and facts and historical tradition in Indo nesian society before the coming of writing with an instrumental version of the patriotic marching song Halo Halo Bandung as the opening and closing musical background resulted from the activities. Two other topics would be developed by groups not yet succeeding in making such media and the MGMP for senior high history teachers hope that similar public service would be held involving other topics or materials.Keywords: science and technology, audio media, teaching media